Hubungan antara Strategi Coping dengan Psychological Well-Being pada Generasi Z - Malinda Pujiati; Komarudin Komarudin (Jurnal Syntax Admiration, 2024)
Coping strategies are individual evaluation methods that can be used to manage behavior in facing problems. This research aims to examine the relationship between coping strategies and psychological well-being among Generation Z. The sampling technique used is purposive sampling, with a research subject of 200 students aged 18-25 years. (69 male, 131 female). The researchers used two scales: the psychological well-being scale adopted from Eva's (2018) study with 18 items and a reliability coefficient of 0.907, and the coping strategies scale with 28 items adapted from Siaputra's (2023) study, which has a reliability coefficient of 0.891. The analysis used is the Pearson Product Moment correlation test, which shows that coping strategies have a strong relationship with psychological well-being, with a correlation score of 0.724. This positive correlation coefficient indicates that the higher the coping strategies, the higher the psychological well-being of students in Yogyakarta. The value of the coefficient of determination (R square) is 0.524, which means that 52.4% of the psychological well-being variable is influenced by coping strategies.